O impacto econômico do agrotóxico na saúde e no meio ambiente nos anos de 2006 e 2017 para a região sudeste do Brasil - Verndl, Natalie (2019)
The present study seeks to analyze the socioenvironmental impacts of agrochemicals, more specifically the organochlorine compound Endosulfan. To do so, the methodologies of economic valuation of the environment will be exposed, where through a hypothetical situation created for the Southeast of the country, a harvest of strawberries is contaminated by the compound, in proportions doubled to the established ideal. This fact could occur due to human error or mechanical error, and especially considering the flexibilization of the so-called "Agrochemicals Law" (Federal Law 7.802), this situation could easily occur due to the reduction of inspection. The data used are real and refer to the last complete Agricultural Census of 2006. Looking to update the data, the production of strawberries will be kept constant and the characteristics of income and population will be updated for the year 2017. With the provision of these data and through the methodology chosen and arranged in MOTA; BURSTZYN; JR CANDID; Ortiz (2003), where the methods of valuation of Sacrificed Production and Opportunity Cost are realized, seeking to develop an economic study in the area of environmental economy that meets a social demand, in order to emphasize the importance of strictly necessary use of pesticides, mitigating the health effects of agents and ensuring a concern for the environment. Through this analysis, it is possible to sensitize the agents and the policymakers through the figures obtained, to carry out public policies in this sense, besides emphasizing the importance of establishing the principles of prudence in the allocation of resources, given the importance of the opportunity cost to each age group calculated using age pyramids and the use of the weighted AT-2000 Actuarial Table for the year 2006 and 2017